Natural hybridization potential in mesquite (Prosopis laevigata and P. glandulosa var. torreyana, Leguminosae) from the Altiplanicie de San Luis Potosí - Galindo Almanza, Sergio; Garcia Moya, Edmundo; Wendt, Thomas L.; Gonzalez Cossio, Felix V. (Instituto de Ecología, A.C., 1995)
The purpose of this study is to demonstrate that hybridization occurs between mesquite species (Prosopis laevigata (Humb. & Bonpl. ex Willd.) Johnst. and Propsopis glandulosa var. torreyana (L. Benson) Johnst.) in the highlands of San Luis Potosí. We found no geographic, ecological, phenological, pollination, chromosomal or compatibility barriers to interspecific hybridization. Morphological evidence of natural hybridization was observed, and by artificial crosses hybrids were obtained.